Evaluation of Zakat Management Program in The Badan Amil Zakat National of Banten Province - Muammar, Ahmad Nurul; Widodo, Joko; Sulhadi, Sulhadi (Journal of Research and Educational Research Evaluation, 2018)
In the Islamic religion of zakat one of the pillars required for every Muslim (As'ad, 1980: 01), Hasan (2010) defines that zakat has a special place on Islamic principles, and is the main tool for ensuring social justice in Islam. The purpose of this research is to make the evaluation instrument of zakat management program at Badan Amil Zakat Nasional (BAZNAS) Provinsi Banten fulfilling valid condition and effectiveness assessment test with evaluation of Context Input Process Product (CIPP) model. This research using Mixed Methods is a procedure for collecting, analyzing, and "mixing" quantitative and qualitative methods in a study or series of studies to understand the research problem based on Cresswell & Plano Clark's opinion. Data collection techniques with documentation studies, interviews and questionnaires. The result of the research is the product of evaluation instrument of zakat management program equipped with lattice, validation sheet, and scoring guidance. Analysis of validity test based on validity test of instrument performed by construct validity test by requesting consideration or expert judgment through instrument validation sheet which then analyzed using delphi technique. The result of the validation study is considered very effective to evaluate the zaltat management program at national institution / institution / national agency. It is based on the average score on all aspects of expert judgment reaching 78.3% (very good). Individually every aspect of the effectiveness assessment is between 86% - 93%. Percentage analysis results, the scale of assessment criteria is very appropriate or very good that is between 91% - 100%.